Commercial Scale Cucumber Fermentations Brined with Calcium Chloride Instead of Sodium Chloride. Issue 12 (29th October 2015) - Pérez‐Díaz, I. M.; McFeeters, R. F.; Moeller, L.; Johanningsmeier, S. D.; Hayes, J.; Fornea, D. S.; Rosenberg, L.; Gilbert, C.; Custis, N.; Beene, K.; Bass, D.
Abstract: Development of low salt cucumber fermentation processes present opportunities to reduce the amount of sodium chloride (NaCl) that reaches fresh water streams from industrial activities. The objective of this research was to translate cucumber fermentation brined with calcium chloride (CaCl2 ) instead of NaCl to commercial scale production. Although CaCl2 brined cucumber fermentations were stable in laboratory experiments, commercial scale trials using 6440 L open‐top tanks rapidly underwent secondary cucumber fermentation. It was understood that a limited air purging routine, use of a starter culture and addition of preservatives to the cover brine aids in achieving the desired complete cucumber fermentation. The modified process was used for subsequent commercial trials using 12490 and 28400 L open‐top tanks packed with variable size cucumbers and from multiple lots, and cover brines containing CaCl2 and potassium sorbate to equilibrated concentrations of 100 and 6 mM, respectively. Lactobacillus plantarum LA0045 was inoculated to 10 6 CFU/mL, and air purging was applied for two 2–3 h periods per day for the first 10 d of fermentation and one 2–3 h period per day between days 11 and 14. All fermentations were completed, as evidenced by the full conversion of sugars to lactic acid, decrease in pH to 3.0, and presented microbiological stability for a minimum of 21 d. This CaCl2 process may be used to produce fermented cucumbers intended to be stored short term in a manner that reduces pollution and waste removal costs.